Measuring Human Capital in Europe and Central Asia - Demirguc-Kunt, Asli (World Bank, Washington, DC, 2020)
This paper outlines an extension of the Human Capital Index that addresses the specific challenges in education and health faced by countries in Europe and Central Asia. Good basic education will not be enough, as job markets today demand higher levels of human capital than in the past. As the region’s population becomes older, it is important that adults remain healthy to ensure productive aging. The Europe and Central Asia Human Capital Index (ECA-HCI) extends the Human Capital Index by adding a measure of quality-adjusted years of higher education to the original education component, and it includes the prevalence of three adult health risk factors -- obesity, smoking, and heavy drinking -- as an additional proxy for latent health status. This extension of the Human Capital Index could also be useful for assessing the state of human capital in middle-income countries in general.